Critical failure mechanisms in relatively flat undrained slopes. Issue 2 (16th June 2020) - Griffiths, D.V.; Martin, C.M.
Abstract : Undrained slope stability analysis has been one of the most frequently studied theoretical problems in geotechnical engineering. The classical charts of Taylor, based on strictly circular failure mechanisms, are generally accepted to give accurate stability numbers (and hence factors of safety) for a wide range of slope geometries, including slope angles as low as 5°. Recent studies using limit equilibrium methods have observed that a more critical failure mechanism for some undrained slopes is non-circular, with curved ends connected by a translational section running along the firm base. This paper focuses on assessing the stability of relatively flat undrained slopes using the methods of finite-element limit analysis and elastic−plastic finite-element analysis, which involve no a priori assumptions about the form or location of the critical failure mechanism. Slopes with inclinations of 5 and 10° are considered in detail and it is shown that the critical failure mechanisms in these cases can be far from circular, with stability numbers differing by as much as 12% from those obtained by assuming a circular mechanism.